Photonic Inverse Design of Simple Particles with Realistic Losses in the Visible Frequency Range - Valagiannopoulos, Constantinos (Photonics, 2019)
Billions of U.S. dollars of basic and applied research funding have been invested during the last few years in ideas proposing inverse concepts. The photonics market could not make an exception to this global trend, and thus, several agenda-setting research groups have already started providing sophisticated tools, constrained optimization algorithms, and selective evolution techniques towards this direction. Here, we present an approach of inverse design based on the exhaustive trial-and-testing of the available media and changing the physical dimensions’ range according to the operational wavelength. The proposed technique is applied to the case of an optimal radiation-enhancing cylindrical particle fed by a line source of visible light and gives a two-order increase in the magnitude of the produced signal.